Peralatan Hidup dan Teknologi dalam Novel Haniyah dan Ala di Rumah Teteruga Karya Erni Aladjai - Latifah, Suci Ayu; Wahyuni, Sri; Setiawan, Agus (Jurnal Bahasa dan Sastra, 2024)
Literature is an eternal cultural representation in written form. The novel Haniyah and Ala at Teteruga’s House was written by Erni Aladjai to perpetuate the culture of eastern Indonesia. This study aims to describe the living equipment and technology in the novel. This is interesting because novels are attached to relics that are rarely owned by modern society. The anthropological theory of literature is assisted in exploring the culture of life tools and technology. Descriptive qualitative research methods are applied to find cultural aspects in each storytelling of the novel. Furthermore, the data collection technique of observing, reading and taking notes is carried out as a step before conducting content analysis. The results of the research findings are the existence of living equipment and technology such as (i) clothing, (ii) shelter, (iii) relics, (iv) weapons, (v) production objects, (vi) transportation in the form of boats, and (vii) agricultural equipment. Through these findings, it can become a cultural discourse for readers, as well as a scientific anchor regarding local wisdom and locality.